2006
DOI: 10.1016/j.exer.2005.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of retinal damage in the episcleral vein cauterization rat glaucoma model

Abstract: Episcleral vein cauterization (EVC) is used in rats to generate a glaucoma model with high intraocular pressure (IOP). The long-term retinal damage in this glaucoma model however, has not been accurately quantified. We report the location and amount of retinal ganglion cell (RGC) damage caused by (EVC) induced IOP elevation in two rat strains.IOP was raised in one eye of Wistar(N=5) and Brown-Norway(B-N)(N=7) rats by EVC and monitored monthly until IOP in contralateral eyes equalized at 5 months post-surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 21 publications
(29 reference statements)
6
49
0
Order By: Relevance
“…Danias et al have recently reported RGC estimates using automated counts of retinal whole mounts with a range of 57,978 to 88,131 (mean of 73,490) RGCs (Danias et al, 2006). Although slightly lower, both estimates are well correlated with our current result of a range of 79,748 to 93,422 RGCs (mean of 86,282) estimated by crosssectional stereological counting.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Danias et al have recently reported RGC estimates using automated counts of retinal whole mounts with a range of 57,978 to 88,131 (mean of 73,490) RGCs (Danias et al, 2006). Although slightly lower, both estimates are well correlated with our current result of a range of 79,748 to 93,422 RGCs (mean of 86,282) estimated by crosssectional stereological counting.…”
Section: Discussionsupporting
confidence: 81%
“…Cross-sectional stereological counting produces highly accurate and reproducible counts. Standard deviations were less then 7% of total RGCs mean in all animals, comparable to previous RGC estimates by axonal count (9%) (Cepurna et al, 2005) and whole mount counts (12%) (Danias et al, 2006).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Studies modeling the impact on common neurotoxicity pathways by substances like kainate, glutamate and NMDA, showed that higher sensitivity of LRGCs that suffered faster degeneration compared to SRGCs in rat both vivo and in vitro (Dreyer et al 1994;Sucher et al 1997;Vorwerk et al 1999). A size-dependent sensitivity has been consistently detected in rat models of experimental intraocular pressure-induced glaucoma (Glovinsky et al 1991;Glovinsky et al 1993;Sucher et al 1997;Quigley 2005;Danias et al, 2006); and a similar size-dependent susceptibility to glaucoma has been reported for human RGCs, where a population of LRGCs and corresponding large axons were lost faster than SRGCs and smaller axons (Glovinsky et al 1991;Chaturvedi et al 1993;Glovinsky et al 1993;Sucher et al 1997;Isenmann et al 2003;Quigley 2005).…”
Section: Introductionmentioning
confidence: 99%